DIGITALISASI PENDIDIKAN DAN KUALITAS INTERAKSI SOSIAL SISWA KELAS X SMK TARUNA HARAPAN 2 - Eka Martiani; Maryati; Siti Sarah Nur Fatahilah; Intan Rustianti; Alfiah Putri Nursaidah (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2026)
Digital transformation in education has transformed the learning process in the Society 5.0 era, but its impact on the social interaction of students in rural schools still needs more in-depth study. This study aims to analyse the dynamics of students' social interaction in the implementation of digital learning in class X of SMK Taruna Harapan 2, West Bandung Regency. The study used a descriptive qualitative approach with observation techniques, in-depth interviews, and documentation of 27 informants consisting of 20 students and 7 teachers. The results of the study show that the use of Google Classroom, WhatsApp, Zoom, and Canva increases the effectiveness of learning, participation, and student confidence in discussions. However, limited devices and internet networks are still obstacles that cause learning participation gaps. In addition, the dominance of digital communication tends to reduce the intensity of face-to-face interactions, thus affecting the emotional closeness between students. This study concludes that digitalisation makes a positive contribution to the quality of learning, but it needs to be supported by equitable access to technology, the application of blended learning models, and the strengthening of digital literacy and ethics so that digital transformation can improve the quality of learning while strengthening students' social interaction inclusively.